Heteronome Subjektivität: Dekonstruktive und hermeneutische Anschlüsse an die Subjektkritik Heideggers - Eldracher, Martin (transcript, 2018)
Thinking in concurrence with and in opposition to Heidegger's critique of the subject – this volume shows that an understanding of heteronomous subjectivity is based on the fact that the impossibility of self-transparency is the very possibility of freedom.